The 'cello' in the low countries: the instrument and its practical use in the 17th and 18th centuries 1-3/3 - Tinbergen, Elske (Leiden Universiteit Leiden, 2018)
What was the name, the appearance, development and the playing technique of the cello in the Low Countries between 1600 and 1800 and what music was composed for it?This question has been divided into four sub-questions, each of which are dealt with in one chapter of this dissertation.In Chapter 1 I have investigated whether in written sources information is to be found about the name of the cello, and possible additonal information about the tuning of the strings and the technique.Chapter 2 is based on a research corpus of over 850 17th and 18th-century representations of cellos and cellists (reproduced in Part 2 of this dissertation). The following characteristics of the cello were scrutinized: size, scroll, shoulders, sound holes, frets, material and number of strings and the colour of the hairs of the bow, as well as how the instrument was played (how is the instrument held, the way the bow is held and the position of the left hand). The database with all results is reproduced in Part 3.A case study about French instruction drawings meant for a cello method has also been added. The depicted technique here has been compared with that on Dutch images to determine how realistic the Dutch images are.Chapter 3 focuses on the instruments still present in museums and private collections. An important question was whether the characteristics of these instruments are to be found on the images presented in Chapter 2.Chapter 4 is divided into two Sub-chapters, about the music from the 17th and music from the 18th century respectively. By including the results from Chapter 1, I examined whether the name of the instrument, as mentioned in the 17th-century music, can shed light on which instrument should be used to play the bass line.As for the 18th-century music: of the majority of the books containing sonatas for cello solo and basso continuo or for two cellos only a short description has been given. The composer Alexis Magito, however, has been researched more thoroughly, since until now hardly anything was known about him. The results of this research have been presented as an extensive case study.The name 'cello' is a common term used mistakenly for the entire period of my dissertation. Therefore the word cello was placed between inverted commas in the title. The most correct term would be: 8' bass instrument of the violin family. Since this description is too long to use each time, I have chosen, when speaking generally, to name the 17th-century instrument 'bass violin' and the 18th-century instrument 'cello'.In general the conclusion may be drawn that during the period studied the cello was used far more in the Low Countries than 20th-century literature wants us to believe. Instruments were built, very many images were produced and also a sizable collection of music for cello was composed (cello as continuo instrument (possibly obligato) or as solo instrument).The most surprising outcome has been that, in comparison to what was previously thought, the underhand bowing was used extensively. Moreover I found a lot of information about the composer, cellist and engraver Alexis Magito and I could date his sonatas more precisely than had been possible until now.It is very important that (baroque) cellists examine the results of this research. It shows that also in the Low Countries the cello was widely used, that the instrument had many different characteristics and that it was played in many different ways.
Proefschrift ter verkrijging van de graad van Doctor aan de Universiteit Leiden op gezag van de Rector Magnificus prof. mr. C.J.J.M. Stolker, volgens besluit van het College voor promoties te verdedigen op 13 juni 2018